2016
DOI: 10.1097/fjc.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacogenetics in Atrial Fibrillation Therapeutics

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia worldwide requiring therapy. Despite recent advances in catheter-based and surgical therapy, antiarrhythmic drugs (AAD) remain the mainstay of treatment for symptomatic AF. However, response in individual patients is highly variable with over half the patients treated with rhythm control therapy experiencing recurrence of AF within a year. Contemporary AADs used to suppress AF are incompletely and unpredictably effective and associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 126 publications
0
16
0
1
Order By: Relevance
“…These variants frequently require further classification to confirm or eliminate their pathogenicity. Genetic predisposition may influence the response to AF therapies (Darbar et al, 2007 ; Parvez et al, 2012 ; Benjamin Shoemaker et al, 2013 ; Huang and Darbar, 2016 ) and can allow specific and based-mechanism therapies (Roberts and Gollob, 2010 ; Campbell et al, 2013 ; Faggioni et al, 2014 ; Darbar, 2016 ).…”
Section: Af Pathophysiologymentioning
confidence: 99%
“…These variants frequently require further classification to confirm or eliminate their pathogenicity. Genetic predisposition may influence the response to AF therapies (Darbar et al, 2007 ; Parvez et al, 2012 ; Benjamin Shoemaker et al, 2013 ; Huang and Darbar, 2016 ) and can allow specific and based-mechanism therapies (Roberts and Gollob, 2010 ; Campbell et al, 2013 ; Faggioni et al, 2014 ; Darbar, 2016 ).…”
Section: Af Pathophysiologymentioning
confidence: 99%
“…Ideally, such electrophysiological differences can be exploited in the future to improve the efficacy and safety of AAD therapy. For example, initial data have suggested that pharmacogenetic-guided selection of Class I vs. Class III drugs in patients with AF may improve the response to AAD therapy [39, 40]. This approach is currently being tested in a preliminary feasibility study (NCT02347111).…”
Section: General Considerations For Novel Antiarrhythmic Drugsmentioning
confidence: 99%
“…A large number of potential antiarrhythmic targets and agents have been discussed in a number of excellent recent review articles. For example, several reviews have focused on atrial-selective K + -channel blockers for AAD therapy in AF [34, 35, 36], AADs against atrial and ventricular arrhythmias targeting Ca 2+ -handling abnormalities [42, 43], or personalization of AAD therapy [40]. Here, we focus on several targets and the agents directed against these targets that have received considerable attention during the last few years.…”
Section: Promising Antiarrhythmic Targets and Agentsmentioning
confidence: 99%
“…However, even for a given AF type, there is substantial patient-to-patient variability in the clinical presentation, ranging from numerous short-lived AF episodes to few but long-lasting episodes, and from completely asymptomatic to severely symptomatic patients [1,5] Challenges to the translation of basic science findings to atrial fibrillation therapies EDitORial of AF complexity may facilitate a more stratified approach. ECG biomarkers of AF complexity can predict long-term success of catheter ablation [16] and tailored therapy based on genetic information might also be possible and is currently being evaluated based on genetic variants near the PITX2 gene [17]. Nonetheless, extrapolating genetic alterations to AF mechanisms in patients remains challenging.…”
Section: • • the Etiology Of Af Patients Is Highly Heterogeneousmentioning
confidence: 99%